Proceedings of the 6th International Workshop on Realizing Artificial Intelligence Synergies in Software Engineering 2018
DOI: 10.1145/3194104.3194106
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the benefits of utilizing conceptual information in test-to-code traceability

Abstract: Striving for reliability of software systems often results in immense numbers of tests. Due to the lack of a generally used annotation, finding the parts of code these tests were meant to assess can be a demanding task. This is a valid problem of software engineering called test-to-code traceability. Recent research on the subject has attempted to cope with this problem applying various approaches and their combinations, achieving profound results. These approaches have involved the use of naming conventions d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…For instance, for identifying Lazy Test [46], we need to know the production files and classes that correspond to it. Numerous recent studies have examined the topic of test-tocode traceability [28], [29], [25], and a wide range of approaches have been proposed. Nonetheless, establishing a dependable 1-to-1 relationship between a production method and a test method within the context of static analysis presents a challenge [29].…”
Section: Selecting Test Smellsmentioning
confidence: 99%
“…For instance, for identifying Lazy Test [46], we need to know the production files and classes that correspond to it. Numerous recent studies have examined the topic of test-tocode traceability [28], [29], [25], and a wide range of approaches have been proposed. Nonetheless, establishing a dependable 1-to-1 relationship between a production method and a test method within the context of static analysis presents a challenge [29].…”
Section: Selecting Test Smellsmentioning
confidence: 99%
“…Lack of generally used annotation of artifacts (Kicsi et al, 2018) and imperfectly appropriate naming (Csuvik et al, 2019b) typically lead to inaccurate links. The added challenge of artifacts, such as non-functional requirements (Mahmoud and Williams, 2016), hinders traceability efforts due to the lack of homogeneity in syntax representation: natural language pertaining to nonfunctional requirements is less explicit in tracing links.…”
Section: Syntax Conventionmentioning
confidence: 99%
“…Thus, our results were evaluated on eight real programs and also using a variety of source code representations and settings. Our work aimed to show that LSI itself performs better than it had been previously perceived by the research community [75], investigated the question of source code representations in the task, and also found that Doc2Vec can significantly outperform LSI [31] while a suitable combination of the textual similarity techniques could provide even better results [30].…”
Section: The Proposed Methodsmentioning
confidence: 99%
“…While test-to-code traceability is not the most widespread topic amongst recovery tasks, several well-known approaches aim to cope with this problem. Still, as yet, none of them has provided a perfect solution for the problem [61,132,75,126,31,30]. The current state-of-the-art techniques [125] rely on a combination of diverse methods -i.e.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation